Collaboration and Performance in Handling Earthquake, Tsunami, and Liquefaction Disasters with Palu City Government - Daswati, Daswati; Hattab, Syahruddin (Universitas Negeri Makassar, 2022)
Research related to disasters has recently been carried out by all institutions and individuals, including international researchers because this has become a very important global issue and needs to be followed up through research. Considering that the earthquake, tsunami and liquefaction disaster that occurred in Palu City on September 28, 2018 attracted the world's attention, this study aims to investigate the collaboration and performance of earthquake, tsunami and liquefaction management of the Palu City government. This study was designed using a quantitative approach with descriptive statistical data analysis and linear regression. The results of the investigation show that collaboration greatly affects the performance of disaster management, especially the ability of the Palu City government to collaborate horizontally with the same level of government organization. Meanwhile, collaboration with non-governmental organizations is still ineffective due to regulatory problems or disaster management mechanisms by the Indonesian government in general, and the Palu City government in particular. This has become the same problem in disaster management, including what happened in previous studies conducted in India, Pakistan, and Bangladesh. For this reason, it is necessary to establish a regulatory framework that can accommodate all disaster problems, especially when disasters occur in the future with the aim of reducing disaster risk.